2010
DOI: 10.4314/sajas.v39i4.51127
|View full text |Cite
|
Sign up to set email alerts
|

Lack of polymorphism in the oocyte derived growth factor (GDF9) gene in the Shal breed of sheep

Abstract: The families of TGF-β proteins are the most important growth factors in the ovary for growth and differentiation of early ovarian follicles. Three related oocyte-derived members of the transforming growth factor-β superfamily, namely GDF9, BMP15 and BMPR-IB have been shown to be essential for follicular growth and ovulation. The aim of the present study was to detect the incidence of mutation in exon two of GDF9 as a major gene in the Shal sheep breed. Blood samples were collected from 239 sheep and genomic DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Our samples were randomly taken from this flock and one would expect to find all possible genotypes of GDF9 if it really segregates in this breed. Moreover, G8 mutation of GDF9 was not detected in small tail Han, Hu, Dorset, Texel and German Mutton Merino sheep (Chu et al 2005), Suffolk, Dorset, Charollais, Romney Hills and Chinese Merino sheep (Guan et al 2007), Cele and Duolang sheep in China (Bai et al 2005), Shal sheep in Iran (Ghaffari et al 2009), Tan sheep in China (Sun et al 2009), Barbarine, Queue Fine de L'Ouest, Noire dehibar, Sicilo-Sarde, D'man sheep in the North Africa (Vacca et al 2010) that is in agreement with the present study. Eghbal Saied et al (2012) discovered that the arisen G4 mutation in Iranian Afshari sheep has led to the maximum ovulation rate compared with other breeds that they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Our samples were randomly taken from this flock and one would expect to find all possible genotypes of GDF9 if it really segregates in this breed. Moreover, G8 mutation of GDF9 was not detected in small tail Han, Hu, Dorset, Texel and German Mutton Merino sheep (Chu et al 2005), Suffolk, Dorset, Charollais, Romney Hills and Chinese Merino sheep (Guan et al 2007), Cele and Duolang sheep in China (Bai et al 2005), Shal sheep in Iran (Ghaffari et al 2009), Tan sheep in China (Sun et al 2009), Barbarine, Queue Fine de L'Ouest, Noire dehibar, Sicilo-Sarde, D'man sheep in the North Africa (Vacca et al 2010) that is in agreement with the present study. Eghbal Saied et al (2012) discovered that the arisen G4 mutation in Iranian Afshari sheep has led to the maximum ovulation rate compared with other breeds that they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the GDF9 gene can be considered as a possible candidate for increased LS in sheep [24]. In the present study, genetic variation were found within the GDF9 gene based on nucleotide sequence for Rahmani and its cross with Barki.…”
Section: Nucleotide Sequence and Amino Acid Sequence Comparisons For mentioning
confidence: 56%
“…Our findings are similar with that revealed by Amiri et al (2007) who did not confirm by using PCR-RFLP the incidence of mutant alleles in FecB gene of LoriBakhtiarin sheep since all samples showed monomorphic genotypes. In coincidence, Kumar et al (2006) in Marwari and Bharat Merino ewes and Ghaffari et al (2009) in Shal sheep observed no genetic polymorphisms in BMPRIB gene by using PCR-RFLP technique. Moreover, Hua et al (2008) studied the genetic polymorphism of Q249R mutation in FecB locus using PCR-RFLP on 550 fecundity Chinese goats such as Boer of different breeds.…”
Section: Discussionmentioning
confidence: 99%